2016
DOI: 10.5935/1806-6690.20160045
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of growth medium and quantification of pollen grains and germination of pear tree cultivars

Abstract: ) and pH (3,5; 4,5; 5,5 and 6,5); 2) sucrose (0; 30; 60 and 90 g L -1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
1
12
1
6
Order By: Relevance
“…after a severe winter (Webster 2002). Confirmation of this finding is a comparison of the discussed outcomes and a study of Nogueira et al (2016). The cultivar 'Hosui', which in our experiment was characterized by a high percentage of pollen germination (90%), exhibited very low germination, at the level of about 19%, in the study of the aforementioned authors.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…after a severe winter (Webster 2002). Confirmation of this finding is a comparison of the discussed outcomes and a study of Nogueira et al (2016). The cultivar 'Hosui', which in our experiment was characterized by a high percentage of pollen germination (90%), exhibited very low germination, at the level of about 19%, in the study of the aforementioned authors.…”
Section: Resultssupporting
confidence: 64%
“…Most Asian pear cultivars exhibited high pollen yields, with the exception of six cultivars that contained less than 1000 pollen grains in the anther, which, with a similar number of anthers compared to other cultivars, resulted in Nogueira et al (2016) reported that the cultivar Hosui was characterized by a very low pollen yield, while in our study, this cultivar had a high pollen yield and a similar number of anthers. Quinet et al (2016) reported that the number of pollen grains in the anther of the European cultivar 'Conference' was over 2000, while in the discussed experiment, a slightly lower number of pollen grains was recorded for this cultivar.…”
Section: Resultscontrasting
confidence: 41%
“…Despite the pear is a temperate fruit, there are some cultivars that adapted well in subtropical regions with mild winter, such as hybrid cultivars from Pyrus communis x Pyrus pyrifolia (NOGUEIRA et al, 2016). The main hybrid cultivars exploited in tropical regions in South America are 'Tenra', 'Centenária', 'Cascatence', 'Primorosa' and 'Seleta', launched by the Agronomic Institute (IAC), Campinas/SP (BETTIOL NETO et al, 2014).…”
Section: Implantadas Em Regiões Subtropicais Do Brasil Quanto As Caramentioning
confidence: 99%
“…Uma das formas mais práticas e viáveis de se verificar a fertilidade de grãos de pólen é a germinação dos mesmos in vitro (NOGUEIRA et al, 2015). Para isto, deve-se elaborar um meio de cultura composto por elementos orgânicos e inorgânicos, que reproduzam da forma mais similar possível, as condições oferecidas pela estrutura feminina da flor ao receberem o grão de pólen, sendo desta forma diferente para cada espécie.…”
Section: Introductionunclassified
“…Figueiredo et al (2013) relataram que o ácido bórico é fundamental na germinação de grãos de pólen de amoreirapreta. Nogueira et al (2015) verificaram que a adição de 1.200 mg L -1 de ácido bórico promoveu o incremento de 15% na germinação de grãos de pólen de nespereira, em relação a sua ausência no meio de cultura.…”
Section: Introductionunclassified